THE IMPORTANCE OF INDUSTRY STRUCTURE FOR THE DETERMINATION OF FIRM PROFITABILITY: A NEO‐AUSTRIAN PERSPECTIVE - Hill, Charles W. L.; Deeds, David L. (Journal of Management Studies, 1996)
This paper is concerned with exploring the degree to which industry structure determines firm performance. Most of the business policy literature follows Porter in arguing that industry structure has an important influence on firm level profit rates. the arguments contained in this paper take a counter position. It is argued that a plausible alternative to the hypothesis that industry structure matters is the hypothesis that (holding demand constant) individual firm differences are the most important determinant of firm profitability.